Efektivitas Tugas dan Wewenang Satuan Polisi Pamong Praja Dalam Penegakan Peraturan Daerah - Rahmat Rahmat (Jurnal Litigasi Amsir, 2021)
This research aims to find out how the duties and authority of the civil service police unit are implemented in enforcing regional regulations in Mamuju Regency. Second, to find out what factors influence the effectiveness of the implementation of the duties and authority of the civil service police unit in enforcing regional regulations in Mamuju Regency. In this research, the sampling consisted of 1 member of the Civil Service Police Unit, 10 members of the Satpol-PP, each regional apparatus organization which is a partner of the Satpol-PP in enforcing regional regulations. The research techniques used were interview, observation and literature techniques. The implementation of the Duties and Authorities of the Civil Service Police Unit in Enforcement of Regional Regulations in Mamuju Regency is in accordance with statutory regulations, namely as in the Regional Government Law and technically regulated in Government Regulation Number 16 of 2018 concerning the Civil Service Police Unit, as well as regulated in Mamuju Regent Regulation Number 26 of 2016.